Debtor Data Collection Information System at PT. PNM Pematangsiantar Branch - Erwin Sirait; Sahat Sonang (Information Technology and Science (ITScience), 2020)
This study aims to create a web-based debtor information system at PT. PNM Pematangsiantar Branch. The design and manufacture are intended to facilitate debtor data management. So that employees can easily enter debtor data without having to write it conventionally. Using conventional methods has a negative impact. One of the negative effects of the system that is still in use is data search, data retrieval will take time because you have to open documents one by one. In addition to data search, data collection on prospective debtors wishing to establish a working relationship with companies is also a negative impact from conventional methods. With this application, it is hoped that the processing and data collection of debtor data will be faster and more accurate. The information system to be designed will be in the form of a web and use a MySQL database. It is hoped that this research can solve the problem of debtor information systems at PT.PNM Pematangsiantar Branch.